Self-injurious Behaviors in Posttraumatic Stress Disorder: An Examination of Potential Moderators - Dixon-Gordon, Katherine L. (2014)
BACKGROUND: Despite increasing evidence for a relation between posttraumatic stress disorder (PTSD) and self-injurious behaviors (SIB), limited research has examined the factors that may moderate the associations between PTSD and both nonsuicidal SIB (deliberate self-harm; DSH) and suicidal SIB (suicide attempts). Nonetheless, research suggests that characteristics of the traumatic event, co-occurring borderline personality disorder (BPD), and emotion dysregulation may influence the relations between PTSD and SIB. METHODS: Thus, the aim of this study was to examine the moderating role of these factors in the association between PTSD and SIB (including history and frequency of DSH and suicide attempts, and DSH versatility) among a sample of substance use disorder inpatients with (n = 116) and without (n = 130) a history of PTSD. RESULTS: Results from stepwise regression analyses indicate that sexual assault-related PTSD predicted suicide attempt frequency and DSH versatility among those with PTSD. Furthermore, results from hierarchical linear and logistic regression analyses suggest that co-occurring BPD moderates the relationship between PTSD and both DSH history and versatility and emotion dysregulation moderates the relationship between PTSD and DSH frequency. Specifically, the relations between PTSD and DSH outcomes were stronger among participants with co-occurring BPD and higher levels of emotion dysregulation. LIMITATIONS: This study is limited by its reliance on cross-sectional, self-report data. CONCLUSIONS: Despite limitations, findings suggest distinct risk factors for suicide attempts and DSH, and highlight the importance of examining characteristics of the trauma and associated BPD and emotion dysregulation in assessing risk for SIB in PTSD.